Investigating the effects of biochars and zeolites in anaerobic digestion and co-digestion of cassava wastewater with livestock manure - Achi, C. G.; Kupolati, W. K.; Snyman, J.; Ndambuki, J. M.; Fameso, F. O. (Frontiers in Energy Research, 2024)
The tangible effects of climate change and the influence of environmental factors on climate have driven a shift towards cleaner and more sustainable energy sources. This study investigates the effects of biochar and zeolites in the anaerobic digestion (AD) and co-digestion processes of cassava wastewater (CW) with livestock manure, aiming to assess their impact on methane (CH4) and carbon dioxide (CO2) production, as well as process stability. The study employs design of experiments, analysis of variances, design parameter sensitivity, and differential analysis to explore how varying concentrations of biochar and zeolites influence key production parameters and optimize the overall process. Results indicate that increasing biochar and zeolite concentrations produce alternating effects on CO2 and CH4 generation, with CW significantly contributing to CH4 production. Livestock manure shows similar effects on both gases, necessitating calculated trade-offs in prioritizing one over the other. Findings provide insights into enhancing biogas production and waste management, contributing to sustainable bioenergy and wastewater treatment practices. Numerical results demonstrate that increased biochar concentrations in the co-digestion mixtures increased CO2 and CH4 production rates respectively by an approximate factor of 2, contributing 18% and 5% overall effects respectively. Similarly, zeolite concentrations contributed 9% and 5% overall effects to the production rates of CO2 and CH4 respectively, boosting production rates by factors of 1 and −2. The study’s significance lies in its potential to improve biogas yield and process efficiency, fostering advancements in renewable energy and environmental management.